Tumor-derived exosomal lncRNA-MIR193BHG promotes bone metastasis of breast cancer by targeting the miR-489-3p/DNMT3A signaling axis in osteoclasts - Xiaoya Liu; Rui Ma; Feng Wei; Maihuan Wang; Yiwei Jiang; Peng Zheng; Zhen Cao (Journal of Translational Medicine)
Abstract Background Breast cancer exhibits high incidence and mortality among women, with distant metastasis, especially bone metastasis, being the leading cause of death. Despite advances in adjuvant therapies, bone metastasis remains a challenge for patient survival and quality of life. Exosomes, small vesicles capable of mediating intercellular communication, play a crucial role in tumor metastasis. Results This study investigated the role of tumor-derived exosomal long noncoding RNA (lncRNA)-MIR193BHG in breast cancer bone metastasis. LncRNA-MIR193BHG was delivered to osteoclasts via exosomes and promoted osteoclast formation and activity by targeting the miR-489-3p/DNA methyltransferase 3A (DNMT3A) signaling axis, thereby accelerating breast cancer-induced osteolysis. Knockdown experiments demonstrated that reducing the levels of exosomal lncRNA-MIR193BHG significantly inhibited osteoclast differentiation and bone resorption, which was confirmed both in vitro and in vivo. Additionally, mechanistic studies revealed that lncRNA-MIR193BHG acted as a competitive endogenous RNA (ceRNA) interacting with miR-489-3p, regulating DNMT3A expression and subsequently affecting osteoclast differentiation. Conclusions These findings suggest that lncRNA-MIR193BHG plays a critical regulatory role in breast cancer bone metastasis, and the lncRNA-MIR193BHG/miR-489-3p/DNMT3A signaling axis could be a potential target for the treatment of breast cancer bone metastasis. Future studies should further explore the broader applicability of this mechanism and its clinical feasibility.